2006
DOI: 10.1002/bit.20732
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Decolorization and Detoxification of a Disperse Dye in Textile Effluent by a New Isolate ofBacillus sp.

Abstract: A number of aerobic species capable of decolorizing some of the dyes in a textile mill effluent were isolated. One of the isolates was able to decolorize Terasil black dye under aerobic conditions in the presence of an exogenous carbon source after 5 days. Glucose or starch (%1 ea) are essential for decolorization but the process proceeds faster in the presence of 0.5% yeast extract. Results of the BOD(5) show that the untreated effluent samples have a low BOD value, whereas treated samples show an initial inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(37 citation statements)
references
References 12 publications
2
35
0
Order By: Relevance
“…Our data revealed that the addition of 1% glucose markedly improved the color removal efficiency of textile dye effluent. This is consistent with the previous report (Pourbabaee et al, 2006) that showed a 60% increase of dye decolorization rate in dyeing mill effluent, but it is noted that nitrogen sources tested in this study did not affect the color removal efficiency of textile dye effluent. On the other hand, it is probably impossible to completely decolorize wastewater from textile plant with a single strain, because dye effluent from the textile industry contains a variety of polluting substances including mixtures of different dyestuffs ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our data revealed that the addition of 1% glucose markedly improved the color removal efficiency of textile dye effluent. This is consistent with the previous report (Pourbabaee et al, 2006) that showed a 60% increase of dye decolorization rate in dyeing mill effluent, but it is noted that nitrogen sources tested in this study did not affect the color removal efficiency of textile dye effluent. On the other hand, it is probably impossible to completely decolorize wastewater from textile plant with a single strain, because dye effluent from the textile industry contains a variety of polluting substances including mixtures of different dyestuffs ).…”
Section: Discussionsupporting
confidence: 93%
“…was 56% (Sani and Banerjee, 1999). Pourbabaee et al (2006) recently reported that the maximum reduction of COD in real dyeing mill effluent by Bacillus sp. was 65%, while in the present study its maximum reduction in dye effluent from textile plant by Citrobacter sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, Aspergillus niger had relatively higher % COD and BOD reductions than other bacterial and fungal isolates. Pourbabaee et al (2006) and Andleeb et al (2010) observed similar reductions in COD and BOD in their study of aerobic biotreatment of Terasil black in textile effluent by a newly isolated Bacillus sp. and sulfur black by Aspergillus terreus SA 3, respectively.…”
Section: Resultsmentioning
confidence: 63%
“…A great number of these fungi (especially white-rot fungi) have been shown to excrete extracellular enzymes like lignin peroxidase, manganese peroxidase and laccase (Hatakka, 1994) which catalyze the formation of activated oxygen so that the process of attack on the stable structure of dyes can be initiated. The role of some bacterial and algal species for the decolourization and degradation of textile dyes has also been reported (Jumarkar et al, 2006;Olukanni et al, 2006;Pourbabaee et al, 2006;Togo et al, 2008;Cheriaa et al, 2009). Dyes are removed by biosorption (Fu and Viraraghavan, 2000) and enzymatic mineralization (degradation) by lignin peroxidase, manganese peroxidase, manganese independent peroxidase and laccases (Raaghukumar et al, 1996;Duran et al, 2002;Wesenberg et al, 2003;Svobodova et al, 2006).…”
mentioning
confidence: 73%